An Analysis of the Ordering and Allomorphy of Verbal Inflection in Ayacuchan Quechua from the Distributed Morphology Approach - Martel Paredes, Víctor Arturo (2022)
This article presents a new approach to the (re)ordering of SUBJECT and OBJECT morphemes in verb agreement of Ayacuchan Quechua. Our analysis is based on Distributed Morphology (Halle and Marantz 1993), which proposes operations on morphemes in the morphological component. We conclude that the addressee feature of the second-person OBJECT morpheme –nki «wins» when it comes to specificity and, therefore, it appears in a SUBJECT position, which results in the occurrence of –yki as an allomorph and the appearance of –su. Finally, we propose the occurrence of –su as a transitional defective morpheme, which cannot be considered as a third or second person pronoun.